Subassemblage tests on seismic behavior of double-corrugated-plate shear walls. (1st February 2023) - Tong, Jing-Zhong; Wu, Ruo-Min; Xu, Zhao-Yu; Guo, Yan-Lin
Highlights: Four double-corrugated-plate shear walls (DCPSWs) were tested under cyclic shear loads and stable hysteretic curves were obtained. All specimens achieved drift ratios exceeding 2.0% under cyclic shear loads and showed great energy dissipating capacity. Two typical failure modes were related to the bending and shear deformations. Finite element models were developed and validated against the test results. The inner forces of bolts concerning the aspect ratio of DCPSWs were studied. Abstract: Double-corrugated-plate shear walls (DCPSWs) are shear-resistant and energy-dissipating members newly proposed for applications in medium- and high-rise building structures. In this study, experimental and finite element (FE) investigations were conducted on the DCPSWs. Four specimens were tested under cyclic shear loads, and each achieved a drift ratio exceeding 2.0%. The obtained hysteretic curves showed stable seismic behavior and a high energy-dissipating capacity. Specimens with H-sectional boundary columns exhibited a higher shear resistance and better energy-dissipating capacity than those with flat-plate boundary columns. Two typical failure modes were observed in the tests: (1) low-cycle fatigue failure of the boundary columns and (2) buckling of the embedded plates. In addition, the fracture of corrugated plates near bolted locations is commonly accompanied by buckling deformation of the plates. The related bending and shear deformations were decomposed and studied in detail. Then, FE models were developed and validated against the test results, indicating the validity of the models in simulating the seismic behavior of DCPSWs. The values of the bolt forces concerning the aspect ratios of the DCPSWs were analyzed by obtaining the inner tensile and shear forces of the connecting bolts in FE models. Finally, some design remarks were presented based on the experimental and numerical analyses to provide valuable references for the design of DCPSWs in practice.